Implicature on Trade Banner in Pekanbaru City - Andiana Perizga; Suhardi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
The background of this research is that there are many trade banners in Pekanbaru City that have implied meanings in them. Merchants use implicature in their banners to make the banners more different and interesting for the readers. However, the use of this implicature often violates the principle of maxim of cooperation, which is not conveyed by the implied message between the speaker and the speech partner in the speech on the trade banner. The trade banners have directive implicature functions that contain persuasion, invitation, order and request. This research focuses on the function of directive implicature in trade banners in Pekanbaru City. The purpose of this research is to identify and explain the function of the directive implicature found in banners in Pekanbaru City. This research was conducted in 12 sub-districts in Pekanbaru City, Riau Province. This research lasted for 3 months, starting from June-August 2022. This type of research is descriptive-qualitative research. This data was obtained by taking data using image capture. The data are in the form of sentences contained in banners that have implications. The techniques used in analyzing the data are, (1) Identifying, (2) Classifying, (3) Analysing Data, (4) Presenting, (5) Concluding. Based on the results of the research on implicature in trade banners in Pekanbaru city, there are directive implicature functions intended to instruct, intended to request, intended to persuade, and intended to instruct. The findings of this research are, the function of directive implicature means invitation is the most data, which is 30 data.